Integrasi Nilai-Nilai Kearifan Lokal Nias dalam Pembelajaran Bahasa dan Sastra Indonesia pada Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Nias - Riana Riana (Medan Resource Center, 2026)
The limited integration of local wisdom into higher education learning has reduced opportunities for students to connect academic knowledge with their cultural heritage. This study aimed to examine the effectiveness of integrating Nias local wisdom values into Indonesian Grammar instruction at Universitas Nias. The research employed a Classroom Action Research design based on the Kemmis and McTaggart model, conducted in two cycles involving 55 fourth-semester students. The integration incorporated amaedola (Nias proverbs), hoho texts, and fondrakö values as contextual learning resources. Data were collected through learning achievement tests, classroom observations, and student response questionnaires. The findings revealed a substantial improvement in learning outcomes, with the average score increasing from 58.4 in the pre-cycle stage to 84.6 in the second cycle, accompanied by a learning mastery rate of 89.1%. Student learning activities also improved from 68.5% to 86.3%, while student responses demonstrated a highly positive perception of the instructional approach, with an average score of 4.47. These findings indicate that the integration of Nias local wisdom effectively enhances students’ understanding of Indonesian grammar while simultaneously fostering cultural awareness and appreciation of local heritage. This model offers a promising approach for contextualized learning and is recommended for implementation in other higher education courses.